Scale Up of Biogas Starter Production: Enrichment of Activated Sludge from Biogas for Bio-Hydrogen Production - Septina Is Heriyanti; Joni Prasetyo; Galuh Wirama Murti; Atti Sholihah; Arya Bhaskara Adiprabowo (Program Studi Teknik Kimia, Universitas Pamulang, 2021)
POME as liquid waste from palm oil processing has a high organic content so it is suitable for anaerobic digestion process to produce biogas and bio-hydrogen. This study aims to prepare activated sludge from biogas starter which will be used for bio-hydrogen production. The production of biogas starter with cow dung using POME as feed and the addition of nutrients (urea and DAP) at a certain ratio and buffer (soda ash) was carried out in a fermenter with a capacity of 1 m3 using a fed batch system. During one month of fermentation, methane concentration in biogas increased and stabilized until it reached the highest concentration at 33,7%. The fermentation process also produces hydrogen whose concentration decreases with time because hydrogen-producing microbes are dominant at the beginning of the fermentation, but then the hydrogen produced was consumed by methanogenic bacteria to produce CO2 and CH4. This confirmed that the activated sludge produced from the 1 m3 fermenter contained hydrogen-producing bacteria which were then further processed, one of which was heating at a certain temperature, to suppress the growth of methanogenic bacteria.